Genetic diversity in sweetpotato [Ipomoea batatas (L.) Lam.] in relationship to geographic sources as assessed with RAPD markers - Gichuki, S.T.; Berenyi, M.; Zhang, D.; Hermann, M.; Schmidt, J.; Glössl, J.; Burg, J. (Springer, 2003)
Available evidence shows that sweetpotato originated from either Central or South American lowlands with subsequent dispersal to North America, Europe, Africa, Asia and the pacific islands. A total of 71 polymorphic RAPD molecular markers were used to assess the genetic relationships amongst 74 sweetpotato varieties originating from a total of 23 sweetpotato producing countries within six geographical regions, namely, South America, Central America/Caribbean, United States of America (USA), East Africa, Asia and Oceania. An Analysis of Molecular Variance (AMOVA) indicated that 93.4% of the total variance was due to the differences between genotypes within regions. The difference between regions was significant (P < 0.001) but only contributed 6.6% to the variance. Genetic distance (PhiST) calculated with AMOVA and multidimensional scaling (MDS) revealed that the South American and the Central American/Caribbean genotypes formed two separate clusters. East African varieties, which have unique characteristics from other traditional varieties, were distinct from other traditional varieties from South America and Oceania. These results support the reported hypothesis of the origin and dispersal of the sweetpotato and indicate that the primary centre of diversity probably has two distinct genepools. It is proposed that the dispersal of the sweetpotato from its origin may have mainly involved varieties from Central America/Caribbean as opposed to varieties from South America. There is an indication that new genepools may be evolving in Africa and Asia due to hybridisation and adaptation to the local environments.